Team governance: empowerment or hierarchical control - Friebel, Guido; Schnedler, Wendelin (Journal of economic behavior & organization, 2011)
We investigate the costs and benefits of managerial interventions with a team in which workers care to different degrees about output. We show that if there are complementarities in production and if the team manager has some information about team members, interventions by the manager may have destructive effects: they can distort how workers perceive their co-workers and may lead to a reduction of effort by those workers who care most about output. Moreover, interventions may hinder the development of a cooperative organizational culture in which workers trust each other.
Gesehen am 20.04.2023
Online verfügbar 5. Februar 2011